ИКОНИЧЕСКОЕ СОЗНАНИЕ В ПОЭЗИИ ИВАНА ЖДАНОВА (НА МАТЕРИАЛЕ СТИХОТВОРЕНИЯ ПОРТРЕТ ОТЦА) - Fedorushkov, Edyta (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The paper aims to analyze the original figure of speech, which was described by Ivan Zhdanov as a reverse simile. The figure – due to its similarity – is compared with reverse perspecite used in icon painting. Such a comparison reveals the presence of the iconic consciousness in many layers of Father’s portrait – an exemplary Ivan Zhdanov poem. A meticulous analysis of the poem showed the closeness between the iconic consciousness and the orthodox consciousness which, in turn, is an integral element of Russian culture.